Analys av juverhälsodata från kärnbesättningen Viken - Tufvesson, Emelie (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2007)
Nötcenter Viken is a Swedish nucleus herd for dairy cattle. The goal for the farm is to select suitable mothers for the next top generation of bulls. Today the selection for udder health is based on a pedigree index and phenotype data. The pedigree index is based on the cow's father and grandfathers breeding values. In this study breeding values have been estimated with animal models which also account for the cows own performance.